Memories for the Future? An Ecocritical Reading of Andri Snær Magnason’s On Time and Water. A History of Our Future (2019) - Mose, Gitte (Scandinavistica Vilnensis, 2023)
Andri Snær Magnason’s On Time and Water. A History of Our Future, categorized as a novel when nominated for the Nordic Literary Prize in 2020, is a unique contribution to cli-fi literature and the understanding of climate change. A generic hybrid of autobiography, stories, myths, family- and Icelandic history and culture interwoven with references to international cultures, scientific discussions and evidence-based material, the novel spans times and places and addresses the future. Applying theories from ecocriticism and memory studies, the article explores how the compositional complexity of the book, including its mental time travels, contributes to the production of images of the future.